EFEKTIVITAS PROGRAM SARJANA MEMBANGUN DESA (SMD) DALAM MENINGKATKAN PENDAPATAN PETANI DI KELOMOK TANI TERNAK SAPI WIBUH MANDIRI BATUBULAN KANGIN SUKAWATI GIANYAR - Fatmawati, Anak Agung Sri Manik; Maba, Wayan; Pariartha, I Wayan Wana (Universitas Mahasaarswati Denpasar, 2012)
The aims of the study is to determine the implementation effectiveness of the Sarjana Membangun Desa (SMD) comprehensively in the application aspects of agribusiness livestock of the Wibuh Mandiri cattle farmers groups of the Batubulan Kangin Village, at Sukawati District. This study includes both qualitative and quantitative research. The population in this study were all members of the group of cattle farmers of Wibuh Mandiri as much as 19 persons, informants from the Department of Animal Husbandry, Fisheries and Marine of Gianyar Region 5 persons, and an undergraduate from the SMD program assistant. Data were collected using a questionnaire, both closed questionnaire for the group members and open questionnaire for the the informant. The scoring were as follows; score 3 for the most expected answer (a), while score 1 for the least expected answer (c), and score 2 for the average (b). The data were further analyzed using descriptive statistics to determine the effectiveness of the SMD programs. The results of the study indicated that the respondents assessment of farmers upstream aspects of agribusiness obtained the highest score which is in the percentage of 59.47% meaning very effective, respondents assessment of aspects of agri-cultivation is 55.56% which also mean very effective, and similarly the farmerâs assessment of downstream agribusiness were 54.73% which can also be interpreted very effective. Therefore, it can be concluded that the respondents assessment of the upstream aspects of agribusiness, agribusiness aspects of cultivation, and the downstream agribusiness aspects stated that the SMD program is very effective, both totally as well as the average income per cattle which achieve a more than 50% increase. Given the increase in revenues occurred after the implementation of the SMD program it can be ascertained that the increase in revenue is a result of the very effective implementation of the SMD program. Therefore, it can be concluded that the Village Building Pathways (SMD) is a very effective to increase the income of livestock farmers of the Wibuh Mandiri of the Batubulan Kangin village.